APC/C(Cdh1) enables removal of Shugoshin-2 from the arms of bivalent chromosomes by moderating Cyclin-Dependent Kinase Activity. - Rattani, A; Ballesteros Mejia, R; Roberts, K; Roig, M; Godwin, J; Hopkins, M; Eguren, M; Sanchez-Pulido, L; Okaz, E; Ogushi, S; Wolna, M; Metson, J; et al. (Elsevier, 2017)
In mammalian females, germ cells remain arrested as primordial follicles. Resumption of meiosis is heralded by germinal vesicle breakdown, condensation of chromosomes, and their eventual alignment on metaphase plates. At the first meiotic division, anaphase-promoting complex/cyclosome associated with Cdc20 (APC/C(Cdc20)) activates separase and thereby destroys cohesion along chromosome arms. Because cohesion around centromeres is protected by shugoshin-2, sister chromatids remain attached through centromeric/pericentromeric cohesin. We show here that, by promoting proteolysis of cyclins and Cdc25B at the germinal vesicle (GV) stage, APC/C associated with the Cdh1 protein (APC/C(Cdh1)) delays the increase in Cdk1 activity, leading to germinal vesicle breakdown (GVBD). More surprisingly, by moderating the rate at which Cdk1 is activated following GVBD, APC/C(Cdh1) creates conditions necessary for the removal of shugoshin-2 from chromosome arms by the Aurora B/C kinase, an event crucial for the efficient resolution of chiasmata.